Prevention of Collagen Deposition Following Pulmonary Oxygen Toxicity in the Rat by Cis-4-Hydroxy-l-Proline - Riley, David J. (1980)
Exposure of rats to high oxygen tensions causes increased collagen content of lungs and alveolar enlargement in 3-6 wk. We tested whether cis-hydroxyproline, a proline analogue that inhibits collagen synthesis, could prevent the collagen accumulation and alveolar enlargement. Rats were exposed to hyperoxia for 60 h and then to room air and hyperoxia for alternate 24-h periods for 11.5 d. Treated oxygen-exposed rats received 200 mg/kg cis-hydroxyproline twice daily over the 14-d exposure period. Control rats breathed room air. Examination of lungs on day 14 showed collagen content of oxygen-exposed lungs to be 48% greater than control (P < 0.05). The collagen content of the treated oxygen-exposed lungs was −12% of control (NS). Total lung volume was 16% greater than control in oxygen-exposed rats (P < 0.05) and 8% greater than control in treated oxygen-exposed rats (NS). Morphometric studies showed alveolar size was greater than control in oxygen-exposed rats (188±11 [SE] vs. 143±6 μμl [P < 0.05]). Oxygen-exposed, treated rats had a mean alveolar volume of 150±7 μμl. Lung pressure-volume curves were significantly shifted to the left of control in the oxygen-exposed rats, whereas the curves of the oxygen-exposed, treated group were identical to control. These data suggest that cis-hydroxyproline prevented the accumulation of collagen in the lungs in pulmonary oxygen toxicity. In addition, there was apparent protection from airspace dilatation and decreased lung elasticity, suggesting that alveolar enlargement after oxygen toxicity is linked to the deposition in lung tissue of new connective tissue fibers.